Strategi Manajemen dalam Meningkatkan Daya Saing pada Celebrity Fitness Central Park Mall - Christian Lyonal Wiseno (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This research was conducted to find out the most precise management strategy to enhance competitiveness of Celebrity Fitness Central Park Mall. This study applies a qualitative method, by conducting interviews and also observation by directly reviewing the subject of the study. The analytical method consists Input Stage consisting of Internal Factor Evaluation and External Factor Evaluation, Matching Stage consisting of Strength-Weakness-Opportunity-Threat Matrix and Internal External Matrix, and Decision Stage consisting of Quantitative Strategic Planning Matrix. After analyzing from the existing data, it is known that the Market Penetration strategy is the most appropriate to be implemented for Celebrity Fitness Central Park Mall and Market Development strategy can be used as a support.